2021
DOI: 10.3390/f12010088
|View full text |Cite
|
Sign up to set email alerts
|

The Strong and the Stronger: The Effects of Increasing Ozone and Nitrogen Dioxide Concentrations in Pollen of Different Forest Species

Abstract: The knowledge of pollen sensitivity and tolerance to stress factors such as air pollution is important for forest sustainability, ensuring the most efficient production with the highest benefits and lowest resource losses. This study intended to evaluate the influence of common air pollutants in four forest trees species, Betula pendula Roth, Corylus avellana L., Acer negundo L. and Quercus robur L., through a comparative analysis at the same experimental conditions. We aimed to investigate the effect that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…To this purpose, morphological analysis of the pollen grains is very important. Several studies showed changes in the morphological structure of the cell wall such as shrinkage, thinning, rupture of exine, dilatation of the intine wall and in the pollen wall's constituents such as sporopollenin that can be determinant in the resistance of pollen grains to environmental pollution [34,[43][44][45] (Figure 2). particular attention.…”
Section: Effects Of Air Pollutants On Physical and Chemical Propertie...mentioning
confidence: 99%
See 3 more Smart Citations
“…To this purpose, morphological analysis of the pollen grains is very important. Several studies showed changes in the morphological structure of the cell wall such as shrinkage, thinning, rupture of exine, dilatation of the intine wall and in the pollen wall's constituents such as sporopollenin that can be determinant in the resistance of pollen grains to environmental pollution [34,[43][44][45] (Figure 2). particular attention.…”
Section: Effects Of Air Pollutants On Physical and Chemical Propertie...mentioning
confidence: 99%
“…To this purpose, morphological analysis of the pollen grains is very important. Several studies showed changes in the morphological structure of the cell wall such as shrinkage, thinning, rupture of exine, dilatation of the intine wall and in the pollen wall's constituents such as sporopollenin that can be determinant in the resistance of pollen grains to environmental pollution [34,43,44,45] (Figure 2). In an interesting study, the researchers demonstrated the shrinkage of exine of many species of pollen (Cyperus rotundus, Syzygium cumini, Hyptis suaveolens, Cocos nucifera, Acacia nilotica, Eucalyptus tereticornis, Azadirachta indica and Zea mays) that had been exposed to high concentrations of some pollutants of anthropogenic origin (PMx particles, SO2 and NOx) [46].…”
Section: Effects Of Air Pollutants On Physical and Chemical Propertie...mentioning
confidence: 99%
See 2 more Smart Citations
“…Alterations of BPGs due to atmospheric biochemical reactions with ozone or nitrogen dioxide have been highlighted (Sénéchal et al, 2015). Gaseous air pollutants modify the lipid and protein fraction of BPGs (Farah et al, 2021;Pereira et al, 2021;. Not only pollen grains (PGs) can be modified by air pollution, but there are clear qualitative evidences that allergenic PGs can also act as carriers of pollutants, both adsorbed gases and coagulated particles (Okuyama et al, 2007;Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%